Leveraging : a political, economic and societal framework - Anderson, David M. (Springer International Publishing, 2014)
Leveraging, according to David M. Anderson and his colleagues, is both a basic principle of human conduct and the most dominant strategy in recent years that individuals, organizations and countries use to pursue their ends. Although many scholars agree that a crisis of "over-leveraging" caused the financial crisis of 2008-2010, it has not been appreciated that an "over-leveraging" crisis has existed in American politics and the American family system as well. This book addresses the need for a "Leverage Mean" (falling between the extremes of too much leverage and too little leverage) in the economy, politics, family life, and international relations. It identifies three different kinds of leveraging-bargaining, resource, and investment and provides an explanatory and normative theory which draws on the fields of economics, political science, sociology, history, psychology, international relations, law, and philosophy. Moreover, it shows how the dissolution of the Cold War, the dismantling of the modern family, and the rise of the Internet along with the deregulation of the financial services industry led to the diffusion of power which has made leveraging of the first importance for everyone. This book should be of interest to social scientists, philosophers, political theorists, public policy makers and politicians. David Anderson and his colleagues are the first to characterize and assess one of the major instruments of power of the contemporary era. This volume represents the best work on leverage since Archimedes and will be widely read and discussed. Benjamin Ginsberg, David Bernstein Professor of Political Science and Chair, Center for Advanced Governmental Studies, Johns Hopkins University  Leverage might literally be the operative word of the 21st century. Anderson's volume is a wide-ranging and illuminating study of this fundamental and dynamic concept. Parag Khanna, Senior Fellow, New America Foundation, author of The Second World: How Emerging Powers Are Redefining Global Competition in the Twenty-first Century